Food intake regulation during pregnancy and lactation in mice with reduced activity of the melanocortin system - E. N. Makarova; I. V. Romanova; N. M. Bazhan (Вавиловский журнал генетики и селекции)
Hypothalamic melanortin receptor (MCR) activation inhibits appetite. Neuropeptide Y (NPY) and Agouti Related Protein (AgRP) are coexpressed in some hypothalamic neurons and stimulate feeding, NPY via inhibition of MCR-expressing neurons, and AgRP via MCR4 antagonism. Mutation yellow at the mouse agouti locus (Ау) evokes MCR blockage and stimulates appetite in nulliparous females. The role of MCRs in food intake regulation during pregnancy and lactation is unclear. In this study we measured hypothalamic AgRP and NPY mRNA levels in virgin and mated C57Bl a/a (control) and Ау/a females on days 7, 13, 18 of pregnancy, 10, 21 of lactation, and after offspring separation, AgRP immunoreactivity in virgin and lactating females, and correlated gene expression with food intake (FI). Virgin Ау/a compared to a/a females had higher FI and lower AgRP expression. Pregnant Ау/a and a/a mice showed different patterns of food intake and neuropeptide expressions. NPY mRNA levels increased during pregnancy only in a/a mice, while AgRP mRNA levels increased in both genotypes being lower in Ау/a then in a/a mice. In lactating Ау/a and a/a mice, AgRP expression and NPY mRNA level were similar. AgRP expression was higher in lactating then in virgin Ау/a mice. The results obtained demonstrate that in nonbreeding female mice, MCR blockage is associated with AgRP expression inhibition which vanishes in lactation. In lactation, hyperphagia is independent of MCR blockage. In pregnancy, food intake regulation involves MCR signaling and activation of NPY and AgRP expression.